Exploration of protein engineering methods towards biomaterials, therapeutic protein scaffolds, and localization detection within mammalian cells - Bjerke, Jennifer N., author; Kennan, Alan, advisor; Snow, Christopher, committee member; Williams, Robert M., committee member; Nyborg, Jennifer, committee member (Colorado State University. Libraries, 2019)
Proteins are large biomolecules entangled with complex chemistry that uniquely control the processes, function and efficiency of everyday life. These macromolecules are the final product of the central dogma, and as in any synthesis, the proper reactants must combine in order to produce the correct products. As technologies develop to understand their production and resulting structure, sequence and activities, they have increasingly become a bulk chemical platform in which nearly any desired application can be engineered- ranging from materials to therapeutics. The first half of this dissertation will discuss the potential to break down the central dogma in order to create new biological materials through incorporation of novel building blocks, known as amino acids. The second half will focus solely on the design and analysis of engineered proteins to create scaffolds for biological therapeutics that have the capability to bind almost any disease relevant target. The second chapter of this dissertation describes the synthesis of novel non-canonical amino acids that add new chemistries to any protein of interest. Using amber codon suppression, and careful engineering of tRNA synthetase and cognant tRNA's, these new amino acids can be site selectively incorporated. To start, derivatives of phenylalanine are selected since this machinery has been successfully implemented for many new amino acids. The synthesis of bithiophene explores the utilization of phase transfer catalysis and transition metal cross- coupling to deliver a racemic mixture of the non-canonical amino acid with a bithiophene moiety. The third chapter of this dissertation will discuss the engineering potential of nanobodies, a monomeric protein responsible for all binding interactions, isolated from the variable heavy chain of camelid antibodies. We had previously reported a cationic resurfacing strategy that endowed mammalian cell penetration in three nanobody scaffolds. We have since explored and refined this strategy, along with endowing the capability to bind new targets. In the end we found that, when fused to sfGFP, a polyarginine version (PolyR-NB) increased internalization over the original cationic GFP nanobody (CatNB), but the original CatNB scaffold was more adaptable to extensive mutagenesis. Therefore, the PolyR nanobody scaffold can be utilized to aid the internalization of therapeutic cargo proteins that would otherwise not be able to cross the lipid bilayer, and the CatNB scaffold can become a therapeutic itself, modified to bind any intracellular target of disease relevant proteins. To further prove the later point, the complimentary determining regions (CDRs) of a separate nanobody, the BC2 nanobody, were grafted upon the CatNB framework, keeping all resurfacing and structure intact. Remarkably, the CatNB-BC2 CDR nanobody was able to maintain binding to its wild type partner. The final chapter will showcase the efforts towards development of a facile luminescent assay that detects protein delivery to the cytosol of cells. Adapted from the NanoBit assay developed by Promega to identify protein-protein interactions, our assay utilizes the split nanoluciferase technology to produce a luminescent signal once an exogenous protein has recombined with its other half in the cytosol. This system, in theory, could be applied to identify endosomal release of virtually any therapeutically relevant protein.
Keywords: nanobody; chemical biology; protein engineering